2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6907476
|View full text |Cite
|
Sign up to set email alerts
|

Towards automatic discovery of agile gaits for quadrupedal robots

Abstract: Abstract-Developing control methods that allow legged robots to move with skill and agility remains one of the grand challenges in robotics. In order to achieve this ambitious goal, legged robots must possess a wide repertoire of motor skills. A scalable control architecture that can represent a variety of gaits in a unified manner is therefore desirable. Inspired by the motor learning principles observed in nature, we use an optimization approach to automatically discover and fine-tune parameters for agile ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
(32 reference statements)
0
25
0
1
Order By: Relevance
“…While this is always a concern, given that we have been able to use parameters optimized in simulation on our robot in the past, 8 we believe the results of the simulations are trustworthy. What we found very important is to consider the effect of sensor noise.…”
Section: Optimizationmentioning
confidence: 96%
See 2 more Smart Citations
“…While this is always a concern, given that we have been able to use parameters optimized in simulation on our robot in the past, 8 we believe the results of the simulations are trustworthy. What we found very important is to consider the effect of sensor noise.…”
Section: Optimizationmentioning
confidence: 96%
“…8 The foothold locations are regulated using simple controllers based on an inverted pendulum that keep the robot balanced. The limb coordination and the timings of the swing and stance phases of the legs are parameterized based on the anteroposterior sequence of movement (APS) theory proposed by Abourachid et al 12 This parameterization, as shown in Fig.…”
Section: Control Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the optimization framework used in [22]. The framework is rollout-based and requires many forward simulation of the dynamics.…”
Section: B Optimization Of Individual Trajectoriesmentioning
confidence: 99%
“…The control method can cope with limited sensory information and leads to a large number of gaits, such as forward and lateral walks, trot, pronk and bound as shown in [15]. The controllers are robust against unanticipated perturbations caused by pushes or irregular terrain, but they fail on unperceived slopes larger than 5…”
Section: B Contributionmentioning
confidence: 99%